Exploration of Vocational School Students' Misconceptions of Circle Material - Ros Kristianti; Arif Muchyidin; Budi Manfaat (Journal of General Education and Humanities, 2022)
Misconceptions are ideas not following scientific understanding or understandings coined by experts in a field and can be in the form of an inaccurate understanding of concepts, use of wrong concepts, wrong classification of examples, or confusion of incorrect concepts. Understanding the correct concept is essential because there are still many misunderstandings (misconceptions); therefore, information about misconceptions is needed to avoid continuing misconceptions. This study aims to describe the misconceptions and causes of misconceptions in class XI AP 1 students at a private school in the city of Cirebon on the subject of circle equations. The form of research carried out in this study is qualitative research, with case study research methods. The data collection techniques used are 1) the test method, 2) the method of documenting the results of the answers of students who experience misconceptions, and 3) the interview method carried out on students who experience misconceptions. Based on the data analysis and discussion, it is concluded that 1) There is a misconception about a) the concept of a circle, b) the concept of the radius of a circle, c) the concept of the equation of a circle, and the position of a point on the circle. 2) The causes of misconceptions come from the teacher and the students themselves.